2005
DOI: 10.1017/s0265021505000190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of posture on the incidence of vein cannulation during epidural catheter placement

Abstract: We conclude that there is a direct correlation between the incidence of epidural vein cannulation and patient posture during epidural catheter insertion in parturients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
17
2
Order By: Relevance
“…Although an epidural catheter that has been accidentally placed intravascularly may be identified and repositioned, it also may go undetected [2][3][4]. The increase in inferior vena cava (IVC) pressure may be the predisposing factor for this complication [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an epidural catheter that has been accidentally placed intravascularly may be identified and repositioned, it also may go undetected [2][3][4]. The increase in inferior vena cava (IVC) pressure may be the predisposing factor for this complication [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The preference for patient position during the procedure is variable [16][17][18][19][20][21][22]. In previous studies in non-obese parturients [2,23], a direct correlation was shown between the incidence of epidural vein cannulation and patient position at insertion, with a higher incidence noted in the sitting position, 10.7% versus 6% [23], and 15.7% versus 3.7% [2]. In morbidly obese [body mass index (BMI) 35-39.9 kg/m 2 ] parturients [24], placing the patients in the lateral recumbent head-down position reduced the frequency of epidural venous puncture from 10.7% to 2% and from 12% to 1.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There are extensive vascular plexuses in the epidural space which may be punctured during epidural puncture [1][2][3][4], especially in parturients. Occasionally, blood vessel injuries occur during epidural catheter insertion [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, blood vessel injuries occur during epidural catheter insertion [5][6][7]. The incidence of injuries involving the epidural venous plexus on intravascular (IV) epidural catheter insertion was between 1.3% and 15.7% for obstetric patients; the incidence was higher when the puncture is performed with the patients in the sitting position [2]. Furthermore, inadvertent epidural venous injuries may lead to local anesthetic-induced cardio-or neurotoxicity, a poor anesthetic effect, and even the occurrence of epidural hematomas [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…These epidural plexus changes related to positioning are relevant to the success of neuraxial techniques. When Harney et al 21 randomized 209 parturients to the lateral or sitting position for epidural placement, blood was observed in the catheter 3.7% and 7% of the time, respectively. Similarly Bahar et al 22 , randomizing 900 women to the lateral and lateral Trendelenburg (LT) versus sitting positions, observed lower epidural venous punctures in the lateral and LT positions than in the sitting position ( Table 1).…”
Section: Introductionmentioning
confidence: 99%